Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

With the substitution $$y(x) = \sin x \int u(x) \, dx\tag{*}$$ I managed to get to$$u'(x) = \left(\frac{1}{x}-2\cot x\right)u(x)$$ Solving which gave me $$u(x) = C_1 \frac{x}{\sin^2 x}$$ Inserting that back into $(*)$ $$y(x) = (\sin x) C_1\int \frac{x}{\sin^2 x} \, dx = (\sin x) C_1 \left(\log(\sin x) - \frac{x}{\cot x} + C_2\right)$$

Which doesn't seem to be the correct solution(s). I don't know where I went wrong though.

share|cite|improve this question
up vote 3 down vote accepted

We have a theorem:

There exists a fundamental set of solutions for a homogenous linear 2th-differential equation $a_2(x)y''+a_1(x)y'+a_0(x)y=0$ on an interval $I$.

You have a second order homogenous differential equation which is linear as well. This is essential to have an independent set of solutions $\{y_1(x),y_2(x)\}$ for further aim. As you noted, there is a method in which we can construct a second solution from a known solution such that the latter set is a fundamental set (called reducing the order). It can be proved that if $y_1(x)$ is a known solution then the second one satisfying the theorem is $$y_2(x)=y_1(x)\int\frac{e^{-\int\frac{a_1(x)}{a_2(x)}dx}}{y_1^2(x)}dx$$

So in your equation we have $$y_2=\sin(x)\int\frac{e^{\int\frac{1}{x}dx}}{\sin^2(x)}dx=\sin(x)\int\frac{x}{\sin^2(x)}dx$$ $$y_2=\sin(x)(-x\cot(x)+\ln(\sin(x)))=-x\cos(x)+\sin(x)\ln(\sin(x))$$ Now, your general solution is as $y(x)=C_1y_1(x)+C_2y_2(x)$.

share|cite|improve this answer
Thanks. As it turns out, that was my solution, I just made an error copying it over. – Cubic Jul 1 '12 at 20:16

$$y(x) = \sin(x) \int_0^x u(t) dt \implies y'(x) = \cos(x) \int_0^x u(t) dt + \sin(x) u(x)$$ $$y''(x) = -\sin(x) \int_0^x u(t) dt + \cos(x) u(x) + \cos(x) u(x) + \sin(x) u'(x)\\ = \sin(x) \left( u'(x)-\int_0^x u(t) dt\right) +2 \cos(x) u(x)$$ Hence, $$y''(x) + y(x) = \sin(x) u'(x) +2 \cos(x) u(x)$$ $$-y' + \cot(x) y = -\sin(x) u(x)$$ \begin{align} y''(x) - \dfrac{y'(x)}x + \left(1 + \dfrac{\cot(x)}x \right)y(x) & = \sin(x) u'(x)- \sin(x) \dfrac{u(x)}x +2 \cos(x) u(x)\\ & = \sin(x) \left( u'(x) - \dfrac{u(x)}x\right) +2 \cos(x) u(x) \end{align} Hence, we get that $$u'(x) + \left( 2 \cot(x) - \dfrac1x\right) u(x) = 0$$ Now you should be able to finish it off. Hence, we get that $u(x) = c\dfrac{x}{\sin^2(x)}$. Hence, $$y(x) = c \sin(x) \int_0^x \dfrac{t}{\sin^2(t)} dt$$ The error is in performing the integral. $$\int \dfrac{t}{\sin^2(t)}dt = \log(\sin(t)) - t \cot(t) + k$$ Now you should get the right solution.

share|cite|improve this answer
I get $y''(x) = -\sin(x) \int_0^x u(t) dt + \cos(x) u(x) + \cos(x) u(x) + \sin(x) u'(x)$ - I have no idea where you got the '-' in front of the second cos from. $cx^2\sin x$ can't be the solution because $\sin x$ is a solution. – Cubic Jul 1 '12 at 20:12
@Cubic Sorry. I was wrong. The error is in the integral $$\int \dfrac{t}{\sin^2(t)} dt = \log(\sin(t)) - t \cot(t) + k$$ – user17762 Jul 1 '12 at 20:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.